2021
DOI: 10.1016/j.nut.2020.111123
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the prognostic nutritional index for the severity of coronavirus disease 2019

Abstract: Highlights PNI reflects the immune-nutritional status of patients with COVID-19. PNI decreased with the progress of COVID-19 from common to severe forms. PNI is an inverse and independent factor associated with the severity of COVID-19. PNI < 49 is a cut-off value for predicting the severe form of COVID-19. PNI could be a simple, fast, and effective predictor of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 21 publications
1
54
3
1
Order By: Relevance
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore not surprising that malnutrition should be a common condition among older persons with COVID-19 [99]. Along these lines, if left untreated, it is also associated with a higher mortality [100], making the nutritional counseling especially important in older COVID-19 survivors [101]. This should not only include advice to increase calorie intake, but also to ensure adequate protein, vitamin, and mineral intakes [102].…”
Section: Covid-19-related Acute Sarcopeniatowards Prevention and Managementmentioning
confidence: 99%
“…Healthy nutrition is very important and anyway mistaken or unbalanced diet can be risk factor affecting development of virus pathogenesis. Several research groups have shown that malnutrition or obesity exacerbate COVID-19 disease [35][36][37][38][39]. Therefore, to increase immunity in case of SARS-CoV-2 infection, an optimal diet was recommended with the inclusion of all the necessary nutritional components, trace elements and vitamins [35,[39][40][41][42].…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress Of Virus Infectionmentioning
confidence: 99%